2019
DOI: 10.1002/pros.23755
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate enhances the response of prostate cancer to radiotherapy

Abstract: Background Radiotherapy (RT) is a key therapeutic modality for prostate cancer (PrCa), but RT resistance necessitates dose‐escalation, often causing bladder and rectal toxicity. Aspirin, a prodrug of salicylate (SAL), has been associated with improved RT response in clinical PrCa cases, but the potential mechanism mediating this effect is unknown. SAL activates the metabolic stress sensor AMP‐activated protein kinase (AMPK), which inhibits de novo lipogenesis, and protein synthesis via inhibition of Acetyl‐CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We observed that combined MET + SAL treatment has improved anti-proliferative activity in lung and prostate cancer cell lines in-vitro, compared to each agent alone [33] , but whether this therapy could be effective in-vivo alone or in combination with RT was not studied. Further, we reported the tumor suppressive efficacy of SAL and salsalate in combination with RT in PrCa models [34] , however, salsalate alone did not suppress tumor growth in non-irradiated xenografts.…”
Section: Introductionmentioning
confidence: 91%
“…We observed that combined MET + SAL treatment has improved anti-proliferative activity in lung and prostate cancer cell lines in-vitro, compared to each agent alone [33] , but whether this therapy could be effective in-vivo alone or in combination with RT was not studied. Further, we reported the tumor suppressive efficacy of SAL and salsalate in combination with RT in PrCa models [34] , however, salsalate alone did not suppress tumor growth in non-irradiated xenografts.…”
Section: Introductionmentioning
confidence: 91%
“…Both findings were statistically significant, amongst the 2051 patients treated between 1981 and 2006 with a median definitive radiation dose of 76 Gy. Other preclinical 69 and clinical studies 70 have suggested that that aspirin may benefit the radiotherapy therapeutic index, which may translate to improved overall survival 70 in high-risk prostate cancer patients treated with radiotherapy. Aspirin use during preoperative chemoradiation in colorectal cancer patients may also increase tumor downstaging (67.6 % vs 43.6%, p=−.01), higher progression free survival (86.6% vs 67.1%) and overall survival (90.6% vs 73.2%), as noted in a retrospective study of 241 patients.…”
Section: Aspirinmentioning
confidence: 99%